Exome sequencing to explore the possibility of predicting genetic susceptibility to the joint occurrence of polycystic ovary syndrome and Hashimoto’s thyroiditis - Zeber-Lubecka, Natalia; Suchta, Katarzyna; Kulecka, Maria; Kluska, Anna; Piątkowska, Magdalena; Dabrowski, Michal J.; Jankowska, Katarzyna; Grymowicz, Monika; Smolarczyk, Roman; Hennig, Ewa E. (Frontiers in Immunology, 2023)
A large body of evidence indicates that women with polycystic ovary syndrome (PCOS) have a higher risk of developing Hashimoto’s thyroiditis (HT) than healthy individuals. Given the strong genetic impact on both diseases, common predisposing genetic factors are possibly involved but are not fully understood. Here, we performed whole-exome sequencing (WES) for 250 women with sporadic PCOS, HT, combined PCOS and HT (PCOS+HT), and healthy controls to explore the genetic background of the joint occurrence of PCOS and HT. Based on relevant comparative analyses, multivariate logistic regression prediction modeling, and the most informative feature selection using the Monte Carlo feature selection and interdependency discovery algorithm, 77 variants were selected for further validation by TaqMan genotyping in a group of 533 patients. In the allele frequency test, variants in RAB6A, GBP3, and FNDC7 genes were found to significantly (padjusted < 0.05) differentiated the PCOS+HT and PCOS groups, variant in HIF3A differentiated the PCOS+HT and HT groups, whereas variants in CDK20 and CCDC71 differentiated the PCOS+HT and both single disorder groups. TaqMan genotyping data were used to create final prediction models, which differentiated between PCOS+HT and PCOS or HT with a prediction accuracy of AUC = 0.78. Using a 70% cutoff of the prediction score improved the model parameters, increasing the AUC value to 0.87. In summary, we demonstrated the polygenic burden of both PCOS and HT, and many common and intersecting signaling pathways and biological processes whose disorders mutually predispose patients to the development of both diseases.